Pengaruh Partisipasi Masyarakat Dan Kearifan Lokal Terhadap Minat Berkunjung Di Desa Wisata Kandri Kota Semarang - Julian Andriani Putri; Nina Mistriani; Ray Octafian; Margaretha Setyaningtyas; Gofrandha Hilga Hibatullah; Kafilatul Hidayah (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This study examines the impact of local community engagement and traditional values on the desire to visit Kandri Tourism Village in Semarang, emphasizing the importance of local wisdom and community involvement as key factors. Utilizing quantitative methods and a questionnaire-based survey to collect data from visitors, this research analyzes the influence through multiple linear regression analysis techniques. Findings indicate that both community participation and local wisdom have a positive and significant impact on visiting interest, affirming that improvements in these aspects enhance the desire to visit. The study suggests that the management of tourism villages should focus on active community involvement and the preservation of traditional values to attract more visitors. It offers practical recommendations for destination managers and local authorities to increase community engagement and promote local wisdom as strategies to boost visits to Kandri Tourism Village, showing that synergy between community involvement and traditional values is essential for the successful development and marketing of community-based tourism destinations.